Bioartificial Organ Manufacturing Technologies - Wang, Xiaohong (Cell Transplant, 2018)
Bioartificial organ manufacturing technologies are a series of enabling techniques that can be used to produce human organs based on bionic principles. During the last ten years, significant progress has been achieved in the development of various organ manufacturing technologies. According to the degree of automation, organ manufacturing technologies can be divided into three main groups: (1) fully automated; (2) semi-automated; (3) handworked (or handmade); each has the advantages and disadvantages for bioartificial organ manufacturing. One of the most promising bioartificial organ manufacturing technologies is to use combined multi-nozzle three-dimensional printing techniques to automatically assemble personal cells along with other biomaterials to build exclusive organ substitutes for defective/failed human organs. This is the first time that advanced bioartificial organ manufacturing technologies have been reviewed. These technologies hold the promise to greatly improve the quality of health and average lifespan of human beings in the near future.